2004
DOI: 10.1111/j.1365-2583.2004.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification, cDNA cloning and expression of an insect defensin from the great wax moth,Galleria mellonella

Abstract: An insect defensin, named Galleria defensin, was purified from the larval haemolymph of Galleria mellonella immunized against E. coli. The peptide was composed of forty-three amino acid residues containing six cysteines that might be engaged in intramolecular disulphide bridges. The primary structure of Galleria defensin shared about 90.7% identity to that of heliomicin, which was an insect defensin isolated from Heliothis virescens. The full-length cDNA encoding Galleria defensin was cloned from the fat body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 39 publications
2
63
0
5
Order By: Relevance
“…Previous studies involving the four genes examined in this study have demonstrated that naive insects have a lower expression level when compared to infected insects [10,11]. Galiomicin has been shown to be induced in larvae infected with Escherichia coli and to have antifungal as well as antibacterial activities [24]. Here the expression of galiomicin is higher in infected larvae when compared to mock-inoculated larvae with the highest expression being at 8 and 24 h. Gallerimycin, a cysteine-rich antimicrobial peptide, has been shown to increase in expression when larvae were inoculated with LPS [25] and here the expression in larvae challenged with both yeast isolates and laminarin showed elevated expression from 4 to 24 h. It has been demonstrated previously that transferrin in Drosophila melanogaster is up-regulated upon infection with bacteria [11] and this was also observed here in larvae challenged with sub-lethal doses of C. albicans and S. cerevisiae with the highest transcript level being recorded 24 h postinoculation.…”
Section: Article In Pressmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies involving the four genes examined in this study have demonstrated that naive insects have a lower expression level when compared to infected insects [10,11]. Galiomicin has been shown to be induced in larvae infected with Escherichia coli and to have antifungal as well as antibacterial activities [24]. Here the expression of galiomicin is higher in infected larvae when compared to mock-inoculated larvae with the highest expression being at 8 and 24 h. Gallerimycin, a cysteine-rich antimicrobial peptide, has been shown to increase in expression when larvae were inoculated with LPS [25] and here the expression in larvae challenged with both yeast isolates and laminarin showed elevated expression from 4 to 24 h. It has been demonstrated previously that transferrin in Drosophila melanogaster is up-regulated upon infection with bacteria [11] and this was also observed here in larvae challenged with sub-lethal doses of C. albicans and S. cerevisiae with the highest transcript level being recorded 24 h postinoculation.…”
Section: Article In Pressmentioning
confidence: 68%
“…Induction of expression of immune relevant proteins of G. mellonella by RT PCR Larval RNA was extracted using TRI-reagent at 1,4,8,24 and 48 h post-infection. RNA (2 mg) was treated with DNase I prior to cDNA synthesis using the SuperScript Kit (Invitrogen) with oligo(dT) primers.…”
Section: Insect Larvaementioning
confidence: 99%
“…The function of these fungal proteinases during pathogenesis can be expanded beyond facilitating penetration of the exoskeleton to include utilization of host proteins for nutrition, suppression of host cellular defense, 53 and degradation of host defense molecules. 4,12 from G. mellonella, the defensin-like antifungal peptide 36 and gallerimycin. 37 Confirming the postulated contribution of gallerimycin to antifungal defense in insects, its transgenic expression has been determined to confer resistance to fungal diseases even in crops.…”
Section: Fungal Proteinases As Virulence Factorsmentioning
confidence: 99%
“…It should be noted that inoculation normally occurred after the 24 h of incubation at the three test temperature. The genes that were examined coded for galiomicin, a defensin identified in G. mellonella [19], a cysteine rich antifungal peptide gallerimycin [20], transferrin, an iron binding protein [21] and an inducible metalloproteinase inhibitor (IMPI) from G. mellonella that acts by inhibiting enzymes secreted by pathogenic microbes [22,23].…”
Section: Gene Expression Of Proteins Involved In An Immune Responsementioning
confidence: 99%